KEKUATAN TARIK DAN MODULUS ELASTISITAS BAHAN KOMPOSIT BERPENGUAT SERAT BAMBU DAN FILLER SERABUT KELAPA - Efata Anugrah Harita; Robert Napitupulu; Shanty Dwi Krishnaningsih (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
ABSTRACT The reason for conducting this review is to determine the effect of alkalization on the tensile strength and elasticity of composites of bamboo fiber and coconut fiber with a polyester matrix by varying the NaOH with concentrations of 0%, 2%, and 5%. Alkalization is one of the modifications of natural fibers to develop a compatible fiber-matrix. This exploration strategy uses the hand lay-up technique. In the main cycle, bamboo fiber and coconut fiber were treated without alkalization or 0% alkalization and in the next interaction, bamboo and coconut fiber were soaked in water (2% and 5% NaOH) for 2 hours. Then, at that time, each treatment process was formed into a composite according to the standard tensile test of ASTM D638 – II. The volume portion of bamboo fiber is 15%, coconut fiber is 15% and polyester resin is 70%, and the arrangement of bamboo fibers and coconut fibers is arranged horizontally. The matrix used in this study is a polyester resin matrix of type 157 BTQN with 1% MEKPO hardener. The highest concentration from this review showed that bamboo fiber and coconut fiber composites with NaOH variations of 0%, 2% and 5% respectively had tensile strengths of 34.9 MPa, 34.9 MPa and 54.74 MPa. The highest concentration with 5% NaOH produced the highest tensile strength of 54.74 MPa, while the coconut fiber composite without alkalization had the lowest tensile strength of 34.9 MPa.